2012
DOI: 10.1063/1.4768300
|View full text |Cite
|
Sign up to set email alerts
|

Gold substrate-induced single-mode lasing of GaN nanowires

Abstract: High-power InP quantum dot based semiconductor disk laser exceeding 1.3W Appl. Phys. Lett. 102, 092101 (2013) Chirped InAs/InP quantum-dash laser with enhanced broad spectrum of stimulated emission Appl. Phys. Lett. 102, 091102 (2013) Semiconductor laser monolithically pumped with a light emitting diode operating in the thermoelectrophotonic regime Appl. Phys. Lett. 102, 081116 (2013) Determination of operating parameters for a GaAs-based polariton laser Appl. Phys. Lett. 102, 081115 (2013) GaN-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 20 publications
1
26
2
Order By: Relevance
“…The lasing threshold increase is due to the increase of ambient refractive index, which results in increase of mirror loss and decrease of confinement factor. We note that the measured lasing threshold of the nanotubes is significantly higher than reported for c-axis GaN nanowires fabricated by this two-step top-down approach 6,11 . In order to understand the threshold increase, an eigenmode solver (Lumerical Inc.) was used to simulate the confinement factor and the propagation loss of the transverse modes.…”
Section: Table Of Contents Figurecontrasting
confidence: 55%
See 1 more Smart Citation
“…The lasing threshold increase is due to the increase of ambient refractive index, which results in increase of mirror loss and decrease of confinement factor. We note that the measured lasing threshold of the nanotubes is significantly higher than reported for c-axis GaN nanowires fabricated by this two-step top-down approach 6,11 . In order to understand the threshold increase, an eigenmode solver (Lumerical Inc.) was used to simulate the confinement factor and the propagation loss of the transverse modes.…”
Section: Table Of Contents Figurecontrasting
confidence: 55%
“…In order to maximize the potential of nanowire lasers, a greater understanding and control over their properties, including mode control, polarization control, wavelength tuning, and beam shaping, is necessary. Recently, single mode emission from GaN nanowire lasers was demonstrated via several routes, including size (diameter and length) control 6 , coupled nanowires [7][8][9] , distributed feedback 10 , and placement onto a metal substrate, which induces a mode-selective loss 11 . Wavelength tuning of GaN nanowire lasers was demonstrated using GaN/InGaN nanowire photonic crystal arrays 12,13 , hydrostatic pressure 14 , and bandgap graded nanowires 15,16 .…”
Section: Table Of Contents Figurementioning
confidence: 99%
“…Xu et al, meanwhile, presented results of gold substrate-induced single-mode lasing in GaN nanowires [111]. They showed single-mode lasing and demonstrated that, via the losses due to the gold film, one can discriminate lasing modes such that only one mode will be preferably excited.…”
Section: (B) Hybrid Systems and Heterostructuresmentioning
confidence: 99%
“…Wright et al [14] achieved single-mode lasing using distributed feedback by coupling GaN nanowire lasers to an external dielectric grating. Moreover, single-mode lasing was recently demonstrated from single GaN nanowire lasers when coupled to a lossy metal substrate due to the suppression of the emission from higher order transverse modes [15]. However, the polarization, another key feature essential for many practical applications, apart from a couple of recent studies [16,17] has rarely been studied in nanowire lasers.…”
Section: Introductionmentioning
confidence: 99%